Investigation of Kinesiophobia and Depression Levels of Wrestlers Returning to Sports After Injury - Altunhan, Abdullah; Abanoz, Hasan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The aim of this study is to investigate the kinesiophobia and depression levels of male and female wrestlers in the period following a sports injury. Methods: This study included a total of 433 athletes with a sports injury history at least 6 months ago and the athletes consisted of 174 male athletes who wrestle in Greco-Roman style, 191 male athletes who wrestle in freestyle and 68 females who wrestle in freestyle. The participating athletes in the study were evaluated by the Beck Depression Inventory and Tampa Scale for Kinesiophobia in a one on one interview way. Furthermore, the participants were asked to fill a form that evaluated the information regarding the injuries they had. Results: According to the periods of wrestling history of the wrestlers, depending on the type of activity in which the injury occurred, kinesiophobia and depression levels were determined to be statistically significant between the groups in terms of the injuries that occurred during an exercise or a competition. Conclusion: Following sports injuries, it was determined that depression and kinesiophobia scores were significant. It could be stated that kinesiophobia is not related to the emotional states of athletes.